Application of Clustering and Quantum Teaching Methods as Efforts to Improve Elementary School Students Writing Ability - Kasmawati Kasmawati (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
The purpose of this research is to provide clear information about what, why, and how to learn to write/write using the clustering method and quantum teaching approach. Writing learning activities with the clustering method and quantum teaching approach were carried out in grade V SDN 2 Lamokato Kolaka, starting from curriculum review, program preparation, program presentation, and evaluation. The results showed that: (a) improving the quality of the student learning process seen from the activeness of students in participating in the learning process can be an indicator of the success of learning assessment; (b) the results of the student learning outcomes that reached an average of 8.03, while in the assessment test the average score was only 5.26. Also, the results of statistical analysis using the t-test showed 21,889 results. While the t table price at α = 0.05 is 2.04. Thus, learning writing using the clustering method and quantum teaching approach in class VI SDN 2 Lamokato has significant results; and (c) learning to write/compose using the clustering method and quantum teaching approach is a learning model that can educate students' emotions, activate the right and left hemispheres of the brain, and be able to provide skills to face life in the future.